Pendampingan Simulasi Penggunaan Instrumen Tes Kebugaran Siswa Indonesia (TKSI) di Sekolah Dasar dan Menengah - Bile, Robertus Lili; Yohanes Bayo Ola Tapo; Fransiskus Solanus Dopo (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aimed to enhance teachers’ and students’ understanding of the Indonesian Student Fitness Test (TKSI) as a standardized national fitness assessment. The program was carried out in five partner schools in Golewa District through participatory mentoring and direct simulation. The methods included socialization, training, and field practice involving teachers and students. Data were collected through observation, interviews, and documentation, and analyzed descriptively. The results showed improved teachers’ understanding of TKSI procedures, from equipment preparation to data recording, while students gained direct experience with standardized fitness testing. The simulation-based learning approach supported teachers in mastering technical skills and fostering awareness of physical fitness importance in schools. Outputs included a practical TKSI guide, baseline student fitness data, enhanced teacher competence, and strengthened collaboration between the university and partner schools. This program contributes to improving school-based fitness assessment quality and reinforces physical education’s role in promoting students’ healthy lifestyles.